Ética y filosofía especulativa en el comentario de Tomás de Aquino al Libro I de la Ética a Nicómaco. - Alliende, Clemente Huneeus (Scripta Mediaevalia, 2025)
An interpretation of Aristotle suggesting he advocated for an autonomy of moral knowledge over speculative sciences has become lately widespread. With nuances, similar claims have been made regarding Thomas Aquinas. These readings challenge the description of premodern thought as characterized by a close alliance between speculative and practical knowledge: Understanding the universe and our place in it was considered the first step toward a right government of our own life. This paper collects some passages from Thomas Aquinas' Commentary on the Nicomachean Ethics, particularly from Book I, showing how they read moral theory in light of speculative philosophy. We focus on references to natural teleology, arguments supporting the unity of the ultimate end, the participation of particular goods in a subsistent separate Good, and the ergon argument. Considering these texts, we conclude that Thomas grants only a relative autonomy to practical reasoning, which is ultimately subordinated to speculative wisdom.